Socio-ecological dynamics and inequality in Bogotá, Colombia's public urban forests and their ecosystem services (2015)
Little is known about the distribution of urban forests of rapidly growing megacities in the developing world and what role they have on the well-being of citizens. Lack of information on their spatial distribution and ecosystem service (ESS) provision is especially pressing since megacities are often characterized by irregular land use patterns, social inequities, and socioeconomic instability. We explored spatial equity in key tree structural characteristics and ESS predictors from public urban forests in Bogotá, Colombia. We used one of the most comprehensive public urban tree inventories in Latin America, ESS indicators, and geospatial data to statistically and spatially analyze structural and diversity attributes and provision of ESS across Bogota's land uses and socioeconomic strata. We found that the poorest socioeconomic stratum had the lowest tree size and crown attributes while the wealthiest stratum had the largest trees attributes. Tree diversity was greatest in northern, affluent areas and total C stocks were greatest in residential areas. Potential particulate matter removal was notably proportional to socioeconomic strata with the wealthiest having the greatest potential while the poorest stratum had the lowest. Residential land-use property value premiums were weakly related to tree diameter and height, and locality and socioeconomic strata were the most significant predictors of property value in residential land-uses. We identified marked inequalities in ESS provision by urban trees in Bogotá, Colombia highlighting a need for urban forest ESS to be taken into account in city planning efforts to address environmental justice issues and improve citizen welfare. © 2015 Elsevier GmbH.